Congenital hypodontia of maxillary lateral incisors in association with coloboma of the iris and hypomaturation type of amelogenesis imperfecta in a large kindred - (:unkn) unknown (My University, 1997)
The dental, clinical, genetic, radiological and dermatoglyphic findings in patients from a large kindred with congenital hypodontia of maxillary lateral incisors (CHMLI) in association with coloboma of the iris (Cl) and hypomaturation type of amelogenesis imperfecta (HTAI) are presented. The pedigree of the kindred showing multiple consanguinaeous marriages and the findings of the family members with CHMLI and a family member with CHMLI, Cl and HTAI and two members with both CHMLI and HTAI suggested that the isolated CHMLI was due to an autosomal recessive gene, but, the Cl was determined by an autosomal dominant gene linked to CHMLI gene. HTAI was an autosomal recessive character linked to both CHMLI and Cl.
Keywords: Adult; Female; Humans; Male; Child; Anodontia; Maxilla; Incisor; Abnormalities, Multiple; Coloboma; Iris; Pedigree; Dermatoglyphics; Amelogenesis Imperfecta; Genetic Linkage; Genes, Dominant